The Mindanao I never saw glimpses of "Yutâ sa Saad" from the collections of the Cebuano Studies Center, University of San Carlos - Pacana, Nestor Roa (2010)
Mindanao has attracted visitors since times past. This island had beckoned traders/adventurers, missionaries, colonizers and post-independence homeless and landless lured by the government?s catchphrase ? ?Yutâ sa Saad.?1 From the Spanish colonial period to the American half-century, and to the era of the Philippine Republics, Mindanao never failed to attract divergent colonial and other ?gazes? which not only altered this island?s physiographic features but also its peoples? lives today. This narrative discusses the transformations/representations of some of Mindanao?s places, peoples (particularly the Moros), and their cultures by availing of the collections of the Cebuano Studies Center at the University of San Carlos in Cebu City, and focusing primarily, but not exclusively, on the Nueva Fuerza/ Bag-ong Kusog newspaper of Vicente Rama which saw print from 1915 to 1941.
Includes bibliographical references (page 339).